Karıştırma saldırılarında OFDM-IM tekniğinin performansı - Kaplan, Ahmet (Fen Bilimleri Enstitüsü, 2020)
Son yıllarda gerçekleşen teknolojik gelişmeler nedeniyle veri trafiğinde önemli bir artış yaşanmıştır. Bu hız ihtiyacını karşılamak için dik frekans bölmeli çoğullama (orthogonal frequency division multiplexing, OFDM) tekniği Wi-Fi, LTE, LTE Advanced ve 5G New Radio (NR) gibi birçok telsiz haberleşme standardında kullanılmaktadır. OFDM tekniği sayesinde frekans seçici kanallarda meydana gelen simgeler arası girişimin etkisini azaltmak mümkündür. Ayrıca FFT bloğu sayesinde OFDM tekniği daha basit donanımlar kullanılarak gerçeklenebilir. Ayrıca çoklu-giriş çoklu-çıkış (multiple-input multiple-output, MIMO) teknikleri de artan hız ihtiyacını karşılamak için yaygın olarak kullanılmaktadır. Son yıllarda klasik MIMO yapılara alternatif olarak uzaysal modülasyon (spatial modulation, SM) tekniği araştırılmaktadır. Klasik SM tekniğinde her iletim aralığında yalnızca bir tane anten aktiftir. Bu teknik, bilgi bitlerinin iletimi için hem klasik genlik ve faz modülasyonlarını kullanırken hem de aktif anten indisinden yararlanmaktadır. SM tekniğinde bilgi biti iletimi için kullanılan aktif anten indisi prensibi OFDM tekniğinde alt taşıyıcılar için uygulanabilir. İndis modülasyonlu dik frekans bölmeli çoğullama (orthogonal frequency division multiplexing with index modulation, OFDM-IM) tekniği bilgi iletimi için hem klasik genlik ve faz modülasyonlarını hem de gelen bilgi bitlerine göre belirlenen aktif alt taşıyıcı indislerini kullanmaktadır. OFDM-IM tekniği bilgi iletiminde indis modülasyonundan yararlandığı için aynı bant verimliliği altında bit hata oranı (bit error rate, BER) performansı OFDM tekniğinden daha iyidir. Bilgi güvenliği, haberleşme sistemlerinde göz ününde bulundurulan önemli tasarım parametrelerinden biridir. Özellikle telsiz kanalın yetkili olmayan (illegitimate) birimlere de açık olmasının oluşturduğu zafiyet, telsiz haberleşme sistemlerinde güvenlik önlemlerinin anahtar paylaşımı yanında fiziksel katman etrafında yoğunlaşmasını gerekli kılmaktadır. Bu sebeple bir telsiz haberleşme sisteminin gizli dinleme (eavesdropping), karıştırma (jamming) ve yanıltma (spoofing) gibi fiziksel katman üzerinden gerçekleştirilen saldırılara karşı güvenli olması hedeflenir. Literatürde geniş bant karıştırma (barrage jamming, BJ), kısmi bant karıştırma (partial band jamming, PBJ), tek ton karıştırma, çok ton karıştırma, pilot işarete saldırı gibi farklı saldırı türleri için OFDM tekniğinin performansını inceleyen bir çok çalışma bulunmaktadır. Bildiğimiz kadarıyla karıştırma saldırısı durumunda OFDM-IM tekniğinin performansını inceleyen bir çalışma bulunmamaktadır. Bu tez kapsamında literatürdeki bu eksikliğin kapatılması için OFDM-IM tekniğinin performansı BJ ve PBJ saldırıları durumunda detaylı olarak incelenmiştir. Karıştırma saldırısı durumunda OFDM-IM sisteminin yüksek işaret-karıştırma oranı (signal-to-jamming ratio, SJR) değerlerinde OFDM'e göre daha iyi BER performansı sağladığı gösterilmiştir. Düşük SJR değerlerinde ise OFDM tekniği OFDM-IM'e göre daha iyi BER performansı sağlamaktadır. Ayrıca, yüksek SJR değerlerinde PBJ'nin BJ'ye göre sistemin BER performansını daha çok bozduğu, düşük SJR değerlerinde ise BJ'nin PBJ'ye göre sistemin BER performansını daha çok bozduğu gösterilmiştir. PBJ saldırısı durumunda OFDM-IM sisteminin BER performansını en fazla bozacak olan karıştırıcı-işaret bant genişliği oranı teorik olarak bulunmuştur. Ayrıca esnek karıştırma (arbitrary jamming, AJ) olarak adlandırılan yeni bir karıştırma modeli önerilmiştir. Bu modelde bulunan karıştırma katsayıları değiştirilerek AJ ile OFDM-IM sisteminde yer alan her bir alt taşıyıcıya farklı güçle saldırmak mümkündür. BJ, PBJ ve AJ saldırısı durumunda OFDM-IM sisteminin BER performansı için yüksek işaret-gürültü oranı ve işaret-karıştırma oranı bölgesinde sıkı olan bir teorik üst sınır türetilmiştir. Telsiz haberleşme sistemlerinde kanal kestirimi önemli bir problemdir. Literatürde SM ve OFDM teknikleri için kanal kestirimi konusunda çeşitli çalışmalar bulunmaktadır. Ancak, OFDM-IM tekniği için kanal kestirimi problemini araştıran çalışmaların sayısı yetersizdir. Bu tez kapsamında OFDM-IM sistemine pilot işaret eklenerek karıştırıcının hem bilgi bitlerini ileten OFDM-IM bloğuna hem de pilot işarete saldırdığı durumda, sadece pilot işarete saldırdığı durumda ve sadece bilgi bitlerini taşıyan OFDM-IM bloğuna saldırdığı durumda en küçük kareler (least square, LS) ile lineer minimum ortalama karesel hata (linear minimum mean squared error, LMMSE) kanal kestirim algoritmalarının performansa etkisi araştırılmıştır. Karıştırma saldırısı durumunda LMMSE tekniğinin LS tekniğine göre daha yüksek performansla çalıştığı ve özellikle pilot işaretlere yapılan saldırılara karşı LMMSE tekniğinin LS tekniğine karşı üstünlüğünün çok fazla olduğu gösterilmiştir. Telsiz kanalda çalışan haberleşme sistemlerinde performansı arttırmanın bir yolu da kanal kodlama kullanmaktır. OFDM-IM sisteminin karıştırma saldırılarına karşı dayanıklılığını arttırmak için düşük yoğunluklu eşlik denetim (low density parity check, LDPC) kodları ve blok serpiştirici kullanılmıştır. OFDM-IM ile OFDM sistemlerinin performansı çeşitli kodlama oranları, farklı kod sözcük uzunlukları ve LDPC kod çözücüde farklı algoritmalar kullanıldığı durumlar için bilgisayar benzetimleri yardımıyla detaylı olarak karşılaştırılmıştır. Karıştırma saldırısı durumunda OFDM-IM sistemi için logaritmik olabilirlik oranı (log – likelihood ratio, LLR) hesabı incelenmiştir. LDPC kodlamalı OFDM-IM'in BJ saldırılarına kıyasla PBJ saldırılarına karşı daha dayanıklı olduğu gösterilmiştir. R=1/2 kodlama oranı kullanıldığında BJ saldırısı durumunda OFDM sisteminin OFDM-IM sistemine göre daha iyi bir BER performansına sahip olduğu gözlemlenmiştir. R=3/4 kodlama oranı kullanıldığında ise BJ durumunda OFDM-IM sisteminin BER performansı OFDM sisteminin BER performansına göre daha iyi olmaktadır. Özetle yüksek veri hızlarında OFDM-IM sistemi OFDM sistemine göre BJ saldırılarına karşı daha dayanıklıdır. R=3/4 kodlama oranı için alıcıda logaritmik toplam-çarpım algoritması (logarithmic sum-product algorithm, Log-SPA) yerine Log-Min-Sum algoritması kullanılması durumunda BJ saldırısı altında OFDM-IM sisteminin OFDM sistemine karşı BER performansı üstünlüğünün arttığı gösterilmiştir. Ayrıca Log-SPA ve Log-Min-Sum'ın basitçe değiştirilmiş bir türü olan zayıflatılmış Log-Min-Sum (Att-Log-Min-Sum) algoritmalarının performanslarının birbirine çok yakın olduğu gösterilmiştir. Kodlamalı OFDM-IM ve OFDM sistemlerinin performansı kanal kestirim hatası olduğu durum için de kıyaslanmıştır. Kanal kestirimi hatası durumunda ve BJ saldırısı altında hem R=1/2 hem de R=3/4 kodlama oranları için OFDM-IM sisteminin BER performansının OFDM sisteminden daha iyi olduğu gösterilmiştir. Literatürde bant verimliliği sabit kalacak şekilde klasik OFDM-IM'de kullanılan modülasyon derecesini değiştirerek BER performansını arttıran çeşitli yöntemler önerilmiştir. Bu tez kapsamında klasik OFDM-IM'de kullanılan modülasyonlu işaretlerin daha yüksek dereceli modülasyonlu işaretler ile yer değiştirdiği yüksek modülasyon dereceli OFDM-IM (higher order OFDM-IM, HO-OFDM-IM) tekniğinin BER performansı karıştırma saldırısı durumunda incelenmiştir. Saldırı olmadığı durumda kodlamasız HO-OFDM-IM'in, OFDM ve OFDM-IM'e göre orta ve yüksek SNR bölgesinde daha iyi BER performansına sahip olduğu gösterilmiştir. Ayrıca HO-OFDM-IM, OFDM-IM'e göre düşük SNR bölgesinde de daha iyi bir BER performansına sahiptir. BJ saldırısı durumunda kodlamasız HO-OFDM-IM tekniğinin OFDM ve OFDM-IM'e göre daha iyi BER performansına sahip olduğu gösterilmiştir. Kodlama kullanıldığında, R=1/2 için BJ durumunda hem HO-OFDM-IM hem de OFDM'in OFDM-IM'den daha iyi bir BER performansına sahip olduğu gösterilmiştir. OFDM'in BER performansı ise HO-OFDM-IM'den biraz daha iyidir. R=1/2 kodlama oranı için saldırı olmadığı durumda ve BJ durumunda OFDM HO-OFDM-IM'den biraz daha iyi bir BER performansına sahip olmasına rağmen, PBJ saldırısı durumunda HO-OFDM-IM sisteminin OFDM'e göre daha iyi bir BER performansına sahip olduğu gösterilmiştir. R=3/4 kodlama oranı kullanıldığında ise hem BJ hem de PBJ durumlarında HO-OFDM-IM'in hem OFDM hem de OFDM-IM'den daha iyi bir BER performansına sahip olduğu gösterilmiştir. Ayrıca kodlamalı HO-OFDM-IM sisteminin PBJ saldırılarına, BJ saldırılarına kıyasla daha dayanıklı olduğu gözlemlenmiştir.

Due to technological developments in the recent years, data traffic has increased significantly. To meet the associated data rate requirement, orthogonal frequency division multiplexing (OFDM) technique is used for many wireless communication standards such as Wi-Fi, LTE, LTE Advanced, and 5G New Radio. With the help of the OFDM technique, it is possible to reduce the effect of inter-symbol interference that occurs in frequency selective channels. In addition, OFDM technique can be implemented with relatively simple hardware due to the use of the FFT block. Multiple-input multiple-output (MIMO) techniques are also widely used to meet the increasing speed requirement. In recent years, spatial modulation (SM) technique has been studied as an alternative to the classical MIMO technique. In the classical SM, only one antenna is active in each transmission interval. Both the active antenna indices and M-ary constellation symbol are used to transmit data in SM. SM's principle can be used over subcarriers of OFDM. OFDM-IM (orthogonal frequency division multiplexing with index modulation, OFDM-IM) uses both classical amplitude/phase modulations and active subcarrier indices that are determined according to the incoming information bits to transmit data. Thanks to the utilization of active subcarrier indices to carry information, OFDM-IM achieves a better bit error rate (BER) performance than OFDM under the same spectral efficiency. Information security is one of the important design parameters for communication systems. A wireless communication channel is open and accessible to both legitimate and illegitimate communication nodes. Furthermore, wireless protocols are open to the public, and adversaries can learn transmission parameters and adjust their strategy to disrupt reliable communication effectively. Traditional higher-layer security techniques such as encryption are complex and challenging to implement with the emergence of decentralize network and Internet of Things (IoT) applications that use simple hardware with limited computational capabilities. As a result, communication is vulnerable to physical layer attacks such as eavesdropping, jamming, and spoofing. Especially, mission-critical applications, which will increase with the deployment of 5G and beyond networks, require reliable, secure, and resistant communications. Physical layer security and design can be used to complement and enhance traditional security methods. While OFDM is robust to ISI, it is vulnerable to jamming attacks. OFDM-IM has superior performance when compared to the traditional OFDM at high signal-to-jamming ratios (SJR) under a jamming attack due to the inherently sparse nature of index modulation. In the literature, there are several papers that investigate the performance of OFDM in the presence of different types of jamming attacks like barrage jamming (BJ), partial band jamming (PBJ), pilot jamming, single-tone, and multi-tone jamming. To the best of our knowledge, there is no work dealing with OFDM-IM under the jamming attack. To address this gap, in this thesis, the performance of OFDM-IM is investigated under BJ and PBJ. In the presence of the jamming attack, it has been shown that OFDM-IM system has better BER performance than OFDM at high SJR region, while OFDM system has better BER performance than OFDM-IM at low SJR values. Besides, PBJ affects the BER performance of the OFDM-IM system more than BJ at high SJR values, while BJ affects the BER performance of the OFDM-IM system more than PBJ at low SJR values. In the presence of PBJ attack, the ratio of jamming to signal bandwidth that has the most severe effect on the BER performance of the OFDM-IM system has been theoretically found. Also, protocol-aware smart jammers can degrade the performance of a communication system severely by attacking specific signals or channels such as synchronization signal, reference signal, broadcast, and control channels. For example, in LTE, some control channels such as physical uplink control channel (PUCCH) and broadcast channel (PBCH) are always mapped to the fixed pre-determined subcarriers on the frame. As a result, these channels are vulnerable to smart jammers with a low complexity transceiver. Due to the effectiveness of a smart jammer, it may be used to attack to a communication system. So, in this thesis, a possible smart jammer model called arbitrary jammer (AJ) has been proposed. It is possible to attack to each subcarrier of OFDM-IM with different power by selecting the jamming coefficients independently for each subcarrier. In the presence of AJ, the performance of OFDM-IM has been investigated. An upper bound on the BER performance that is relatively tight at high signal-to-noise ratio and SJR regions has been derived under BJ, PBJ, and AJ. Channel estimation is a significant problem in wireless communication systems. In the literature, there are several papers that investigate the channel estimation for SM and OFDM techniques. However, the contributions of the limited number of papers dealing with the channel estimation problem for OFDM-IM is inadequate. To fill this research gap, in this thesis, performance of the OFDM-IM system is investigated by using pilot signals in the system under the jamming attack. In the case of the jamming attack to the pilot signal and/or OFDM-IM block that transmits the information bits, performance of both least square (LS) and linear minimum mean square error (LMMSE) channel estimation algorithms on the BER performance were investigated. In the presence of the jamming attack, LMMSE has a better performance than LS. Especially, in the case of jamming attacks to pilot signals only, LMMSE has a superior performance in comparison to LS. The error performance of a wireless communication system can be improved by channel coding. Low-density parity-check (LDPC) codes and block interleavers are used to improve the robustness of OFDM-IM system against jamming attacks. The performances of the OFDM-IM and OFDM were compared in detail by means of computer simulations in different coding rates, code block lengths, and LDPC decoding algorithms. Under the jamming attack, the log-likelihood ratio (LLR) calculation for OFDM-IM system was investigated. It has been shown that LDPC coded OFDM-IM system is more robust to PBJ compared to BJ. In the presence of BJ, when R=1/2 coding rate is used, OFDM has better BER performance than OFDM-IM. Besides, under BJ attack, when R=3/4 coding rate is used, OFDM-IM has better BER performance than OFDM. Briefly, OFDM-IM is more robust to BJ than OFDM at high date rates. In the case of using Log-Min-Sum algorithm instead of logarithmic sum-product algorithm (Log-SPA) with R = 3/4 coding rate, BER performance superiority of the OFDM-IM system against the OFDM system is increased under BJ attack. It has been shown that BER performance of the attenuated Log-Min-Sum (Att-Log-Min-Sum) and Log-SPA are almost the same. In addition, the performances of the coded OFDM-IM and OFDM systems have been compared in the presence of channel estimation errors. It has been shown that BER performance of the OFDM-IM system is better than the OFDM system for both R = 1/2 and R = 3/4 coding rates under the BJ attack. In the literature, various techniques that have the same spectral efficiency with OFDM-IM have been proposed to improve the BER performance of the OFDM-IM system by changing the modulation order of the OFDM-IM. In higher order OFDM-IM (HO-OFDM-IM), which is one of the proposed techniques, the modulation order of classical OFDM-IM is replaced by higher modulation order. In this thesis, the BER performance of the HO-OFDM-IM system has been analyzed in the presence and the absence of jamming attacks. It has been shown that uncoded HO-OFDM-IM has better BER performance than OFDM and OFDM-IM in moderate and high SNR regions when there is no jamming attack. Also, HO-OFDM-IM provides better BER performance than OFDM-IM in low SNR region. Moreover, under BJ attack, uncoded HO-OFDM-IM has a superior BER performance over OFDM and OFDM-IM. When R=1/2 coding rate is used, in the presence of BJ, both HO-OFDM-IM and OFDM perform better BER performance in comparison to OFDM-IM. In addition, OFDM achieves slightly better BER performance than HO-OFDM-IM. When R=1/2 coding rate is used, even if the BER performance of the OFDM is barely better than HO-OFDM-IM under both BJ attack and no jamming attack, HO-OFDM-IM has a better BER performance compared to OFDM in the presence of PBJ. Besides, under both BJ and PBJ, HO-OFDM-IM achieves a superior BER performance in comparison to OFDM and OFDM-IM for R=3/4 coding rate. Finally, it has been shown that coded HO-OFDM-IM is more resistant against PBJ than BJ.
Performance of OFDM-IM Under jamming attacks
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilileri Enstitüsü, 2020
Keywords: OFDM tekniği; OFDM technique; kablosuz iletişim; wireless communication